2014
DOI: 10.1017/dmp.2013.112
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Psychological First-Aid Training for Medical Reserve Corps Volunteers

Abstract: PFA training is a promising approach to improve surge responder confidence and competency in addressing postdisaster needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…conducted (Kalanlar, 2018). In another study, on the other hand, the vast majority of students who received training were reported to state they could more easily approach the psychological problems of the victims after the disaster (Chandra et al, 2014). After the training program we implemented, the response self-efficacy of the students in EG for the recovery period was determined to increase.…”
Section: Discussionmentioning
confidence: 99%
“…conducted (Kalanlar, 2018). In another study, on the other hand, the vast majority of students who received training were reported to state they could more easily approach the psychological problems of the victims after the disaster (Chandra et al, 2014). After the training program we implemented, the response self-efficacy of the students in EG for the recovery period was determined to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Training people in PFA improves their confidence in applying it [14] . The Belgian Red Cross-Flanders (BRC) offers basic 3 hours PFA courses to lay people (aiming to prepare them for standardized care), and a 28 hours course to health professionals (aiming to prepare them for individualised care).…”
Section: Introductionmentioning
confidence: 99%
“…11 Similarly, training results in greater reported confidence and perceived capability, which are much needed elements in the effective use of MRC units. 12 Increased self-efficacy is a primary predictor of volunteers' willingness to participate in public health emergency-related activities. 13 Sufficient and timely volunteer training can support risk management practices, promote response capabilities, and increase confidence in performing duties.…”
mentioning
confidence: 99%